EVALUATION OF THE THERAPEUTIC EFFECT OF "TU VAN" GEL IN PATIENTS WITH SUBACUTE AND CHRONIC ATOPIC DERMATITIS - dao, minhchau; Nguyễn Thị Thu , Hằng (Tạp chí Y học Quân sự, 2025)
Objectives: To evaluate the therapeutic effect of "Tu Van" gel in patients with subacute and chronic atopic dermatitis. Subjects and methods: A prospective, open clinical intervention study comparing before and after treatment with "Tu Van" gel on 60 patients with subacute or chronic atopic dermatitis at the Department of Five Senses, Hanoi General Hospital of Traditional Medicine, from July to November 2021. Clinical symptoms were assessed using the Scoring Atopic Dermatitis (SCORAD), Eczema Area and Severity Index (EASI) scales. Results: After 30 days of treatment, itching symptoms at various levels decreased from 83.3% to 33.3% (p < 0.05), and insomnia decreased from 30.0% to 6.7% (p < 0.05); skin lesion symptoms all improved compared to before treatment (p < 0.05). After 30 days of treatment, the overall average SCORAD score decreased from 50.3 ± 15.8 points to 36.8 ± 17.2 points (p < 0.05). The average EASI score decreased from 11.7 ± 9.9 points to 7.3 ± 5.4 points (p < 0.05). Conclusion: "Tu Van" gel has a therapeutic effect on subacute and chronic atopic dermatitis.